Dose board characteristics influence integrated reporting quality? Empirical evidence from an emerging market - Abdallah A.S. Fayad; Arifatul Husna Binti Mohd Ariff; Sue Chern Ooi (Cogent Economics & Finance)
Although scholars and practitioners are recently showing a growing interest in integrated reporting, investigating the variables affecting the integrated reporting quality in Malaysia has not been examined and is still unexplored. This paper aims to fill this gap, by exploring the influence of board of directors’ characteristics on integrated reporting quality in Malaysia. The board’s characteristics considered are size, independence, expertise, gender diversity, and activity, as hypothesized by the agency theory. A total of 64 companies were analyzed from 2017 to 2020, for a total number of 173 integrated reports. The findings highlight that IRQ is positively related to the board size, gender diversity and activity of the board. This study’s finding adds to the current literature in numerous ways, and it contributes to the intensive scientific debate on integrated reporting. Furthermore, it is the first study that investigates such a relationship in Malaysia.